1975
DOI: 10.1017/s0022172400024335
|View full text |Cite
|
Sign up to set email alerts
|

Presence of a dialysable fraction in normal bovine whey capable of killing several species of bovine mycoplasmas

Abstract: SUMMARYMost normal bovine whey samples contain a fraction that survives heating at 560 C. for 30 min., passes through a dialysis membrane and kills a maximum of seven out of ten of the different bovine mycoplasma species tested. Some whey samples appear more active than others but not all affect the same strains of mycoplasma indicating some specificity in their action. Absorption of the active factor from whey by heterologous and homologous mycoplasmas and by erythrocytes was observed. Binding of the factor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1975
1975
1985
1985

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…When subcultured in U3/7.0 broth, the Mayfield clones produced both opacity and an acid pH color change (1.5 pH units) after 3 to 4 days of incubation at 37°C. Unlike M. alvi, the porcine strains produced an acid color change (0.8 pH unit) in glucose serum (GS) broth (pH 7.8) (3). However, acidification in the U3/7.0 broth occurred more rapidly than in GS broth.…”
Section: Resultsmentioning
confidence: 99%
“…When subcultured in U3/7.0 broth, the Mayfield clones produced both opacity and an acid pH color change (1.5 pH units) after 3 to 4 days of incubation at 37°C. Unlike M. alvi, the porcine strains produced an acid color change (0.8 pH unit) in glucose serum (GS) broth (pH 7.8) (3). However, acidification in the U3/7.0 broth occurred more rapidly than in GS broth.…”
Section: Resultsmentioning
confidence: 99%
“…This may reflect the differing ability of mice to deal with inoculated organisms in the early stages of infection. It is possible that humoral mycoplasmacidal factors, similar to those found in bovine whey (Brownlie, Howard and Gourlay, 1974;Howard et al, 1975) might be involved in host defence at this stage of the infection, particularly as neutrophils were found in the glands of only one of five BSVS mice 24 h after inoculation with U. urealyticum T960.…”
Section: Discussionmentioning
confidence: 99%
“…Other in vitro studies on normal bovine milk and whey demonstrated a dialysable factor capable of killing a variety of mycoplasma species, including ureaplasma and M. dispar (Brownlie, Howard & Gourlay, 1974;Howard et at. 1975).…”
Section: Discussionmentioning
confidence: 99%
“…The Ureaplasma sp., strain Vic 9, had previously been shown to induce mastitis in cows (Howard, Gourlay & Brownlie, 1973) and likewise the M. dispar strain Gri 226 (Brownlie et al 1976). The ureaplasma was grown in urea-broth (Howard et at. 1975) and M. dispar in glucose-serum broth (Gourlay & Leach, 1970) containing ampicillin (Andrews et at.…”
Section: Mycopla8masmentioning
confidence: 99%